ISLAM DAN MODERASI BERAGAMA - Muhammad Daffa Handiana; Alfath Tri Hakiqi (PT. Hasba Edukasi Mandiri, 2026)
This study aims to understand the concept of religious moderation from an Islamic perspective and its implementation in daily life. Religious moderation, known in Islam as wasathiyah, represents a balanced, just, and moderate approach to religious practice that avoids extremism (ghuluw). This research employs a qualitative approach using library research methods, examining primary sources such as the Qur'an and Hadith, as well as secondary sources including exegesis books, scholarly texts, and relevant academic journals. The findings indicate that the concept of Islam as a rahmatan lil 'alamin (mercy to all worlds) serves as the primary foundation of religious moderation. The foundational basis of religious moderation in the Qur'an is reflected in Surah Al-Baqarah verse 143, which designates the Muslim community as ummatan wasathan (a justly balanced community); Surah An-Nisa verse 171, which prohibits extremism in religion; and Surah Al-Ma'idah verse 8, which emphasizes justice. Regarding Hadith, Prophet Muhammad SAW forbade excessive behavior in religious matters and stressed the importance of compassion as a principle of moderation. The principles of religious moderation include justice, balance (tawazun), tolerance, and compassion (rahmah). The implementation of religious moderation in daily life can be realized through just behavior in all matters, tolerance toward differences, showing compassion to others, and balancing worldly and spiritual affairs. This study concludes that religious moderation is essential for maintaining interfaith harmony within Indonesia's diverse society, while also serving as a bulwark against extremism and intolerance committed in the name of religion.